2015
DOI: 10.1021/acs.jnatprod.5b00578
|View full text |Cite
|
Sign up to set email alerts
|

Varioxiranols A–G and 19-O-Methyl-22-methoxypre-shamixanthone, PKS and Hybrid PKS-Derived Metabolites from a Sponge-Associated Emericella variecolor Fungus

Abstract: Chemical examination of a sponge (Cinachyrella sp.)-associated Emericella variecolor fungus resulted in the isolation of seven new polyketide derivatives, namely, varioxiranols A-G (1-7), and a new hybrid PKS-isoprenoid metabolite, 19-O-methyl-22-methoxypre-shamixanthone (8), together with nine known analogues. Their structures were elucidated on the basis of extensive spectroscopic analyses, including ECD effects, Mosher's method, X-ray diffraction, and chemical conversion for the determination of absolute co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…The relative configurations at C‐6 and C‐7 were established by the 3 J H,H value as well as the NOESY data. The 3 J H‐6/H‐7 value (7.9) revealed that the anti ‐orientation between H‐6 and H‐7 and the chained structure of 9 adopted a single dominant conformer . Additionally, the NOESY correlations from H‐5 to H‐7 and Me‐12 indicated (6 R *) and (7 R *) configurations ( Figure ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The relative configurations at C‐6 and C‐7 were established by the 3 J H,H value as well as the NOESY data. The 3 J H‐6/H‐7 value (7.9) revealed that the anti ‐orientation between H‐6 and H‐7 and the chained structure of 9 adopted a single dominant conformer . Additionally, the NOESY correlations from H‐5 to H‐7 and Me‐12 indicated (6 R *) and (7 R *) configurations ( Figure ).…”
Section: Resultsmentioning
confidence: 96%
“…The 3 J H-6/H-7 value (7.9) revealed that the anti-orientation between H-6 and H-7 and the chained structure of 9 adopted a single dominant conformer. [21,22] Additionally, the NOESY correlations from H-5 to H-7 and Me-12 indicated (6R*) and (7R*) configurations (Figure 2). Therefore, 9 was determined to be (2E,4E)-6-hydroxy-3,7-dimethyl-8-oxodeca-2,4-dienoic acid, and given the trivial name graphostromol I.…”
Section: Introductionmentioning
confidence: 96%
“…The 1D-NMR afformed the signals of an aromatic nucleus (including two aromatic H-atoms and two phenolic OH groups), two triple methylenes (d(H) 2.78, 2.46), and an ester carbonyl, which accounted for the five degrees of unsaturation ( Table 3). The 1 H, 1 H-COSY correlations between CH 2 (8) and CH 2 (9), together with the HMBCs from CH 2 (7) to C(1)/C(2)/C(6)/C(9), HO-C(5) to C(4)/C(5)/C(6), and HO-C(3) to C(2)/C(3)/C(4) (Fig. 5) indicated the basic structure of 8, and the Cl-atom was located at C(6).…”
Section: Resultsmentioning
confidence: 99%
“…During our ongoing search for bioactive metabolites from marine sponges and fungal endophytes, a sponge‐derived fungus, H. sinuosae (WGCA‐25‐3A), attracted our attention for the AcOEt extract of the fungal culture exhibited cytotoxic activity. Previously, a number of new caryophyllene‐based sesquiterpenoids named punctaporonins H – M were isolated from the fermentation broth of this specimen .…”
Section: Introductionmentioning
confidence: 99%
“…TJ23 was chemically re-investigated. This work gave rise to the isolation and characterization of two new compounds, asperetide (1) and asperanthone (4), and six known compounds, (S)-3butyl-7-methoxyphthalide (2), [10] ruguloxanthone C (3), [11] tajixanthone hydrate (5), [12] tajixanthone methanoate (6), [13] salimyxin B (7), [14] and ergosterol (8; Figure 1). [15] Herein, we described the isolation, structural determination, and biological activity evaluation of the isolates.…”
Section: Introductionmentioning
confidence: 99%